X-ray photoelectron spectroscopy of trihalide ionic liquids: comparison to halide-based analogues, anion basicity and beam damage - Men, Shuang; Lovelock, Kevin; Licence, Peter (Elsevier, 2017)
X-ray photoelectron spectroscopy is used to investigate two 1-octyl-3-methylimidazolium trihalide ionic liquids, with anions including triiodide and iododibromide. The electronic environment of each element present in ionic liquids studied herein is analysed and compared to their halide-based analogous. The anion basicity is compared based upon the measured N 1s binding energy. The iododibromide ionic liquid is studied as a representative sample to illustrate the beam damage effect. Due to the beam damage, there is a new formed bromine component observed. This effect is calculated and demonstrated for all elements present within the ionic liquid. It suggests that the beam induced decomposition caused a stoichiometric loss of bromine atom and iodine atom.